Ex vivo expansion of EPCs derived from human peripheral blood mononuclear cells by Iron-Quercetin complex - Jiraporn Kantapan (2018)
© 2017, Scientific Publishers of India. All rights reserved. Cell-based therapy has emerged as a promising new treatment for cardiovascular diseases. One of the main obstacles to this approach is a limited number of endothelial progenitor cells (EPCs) obtained from the patient and lack of an effective culture-expanded techniques. Thus, we aimed to demonstrate the potential use of paramagnetic agent called “IronQ” (complexation of iron and quercetin) to expand progenitor cells derived from peripheral blood mononuclear cells (PBMCs) fraction and evaluate it as cell labeling probe using magnetic resonance imaging (MRI). PBMCs were cultured in the presence of IronQ complex compared to conventional culture medium. After expansion, cells were characterized by immunostaining, tube formation assay, intracellular uptake of IronQ and visualizing of magnetically labeled cells by in vitro MRI. Our data show that IronQ exerted an effective expansion of the cells by maintaining the progenitor content and increasing the population of angiogenic cells. Intracellular uptake of IronQ increased as time dependent and reached the maximum at 153 ± 95 pg IronQ/cells after labeled for 120 h. The labeled cells demonstrated an increase of MRI signal intensity in T1-weighted image when compared to the signal of unlabeled cells. From these data, IronQ complex could promote the conditions that suitable for the growth of endothelial-specific differentiated cells derived from PBMC fraction, after expansion, the magnetically labeled cells can be visualized and localized by MRI. Our study demonstrated that ex vivo expansion of EPCs fractions derived from PBMCs using the paramagnetic agent IronQ complex might be an alternative method for the treatment of cardiovascular disease.